STEM Education in Early Years: Challenges and Opportunities in Changing Teachers' Pedagogical Strategies - Wai Man Vivienne Leung (MDPI AG, 2023)
In recent years, there have been growing calls to include STEM education in early childhood (EC). This has created new challenges for EC teachers as they try to find ways to integrate STEM content and pedagogical strategies into school-based curricula. This study interviewed 24 EC teachers to understand their roles in implementing STEM education in preschool classrooms. The qualitative interviews explored changes in teachers' roles and challenges before and after integrating STEM-related activities. The study revealed that the STEM education process is a dynamic one, and that the role of EC teachers is changing from one delivering teacher-centered knowledge to one fostering STEM-related learning in children. The research findings indicate that EC teachers face various challenges when implementing STEM education. The transformation of the teacher's role during STEM classroom practices when encountering a range of challenges is discussed.